Modelo teórico-metodológico para el análisis de políticas públicas de fomento al turismo sustentable y la conservación ambiental en el Santuario del Agua Valle de Bravo, México - Ayala-Arzate, Jorge Adonay; Cruz-Jiménez, Graciela; Segrado-Pavón, Romano Gino; Serrano-Barquín, Rocío del Carmen (Pontificia Universidad Católica del Perú, 2025)
The objective is to provide a theoretical-methodological model that analyzes the issues and interventions of the public, social, and private sectors in the design of public policies to promote sustainable tourism and environmental conservation in the Santuario del Agua Valle de Bravo State Park, located in the State of Mexico. Methodologically, the model was developed using both theoretical and empirical elements; the former refers to sustainable tourism as the main category, with sustainability, environmental conservation, and public policies as subcategories. The empirical elements included observation and interviews with key stakeholders involved in tourism and environmental conservation within the park. The model linked these subcategories to structural and positional dimensions, which facilitated engagement with the actors. The comprehensive analysis drew on the assumptions of the Public Policy Network Approach, identifying interaction, coordination, and the exchange of information and resources among the members of the network formed around public policies. The result was a model that serves as a tool for analyzing the reality in these areas by visualizing the connections among those involved in tourism and environmental conservation. It is expected to serve as a reference for addressing various realities in different contexts, while respecting and adapting to their particularities. The model concludes that there are limitations to the scope of public policies in promoting sustainable tourism and environmental conservation in the park, due to a lack of commitment from the public sector to fulfill its responsibilities, as well as limited resources and prevailing interests.

El objetivo es aportar un modelo teórico-metodológico que analice la problemática e intervención de los sectores público, social y privado en el diseño de políticas públicas para fomentar el turismo sustentable y la conservación ambiental en el Parque Estatal Santuario del Agua Valle de Bravo, ubicado en el Estado de México. Metodológicamente, el modelo se integró con elementos teóricos y empíricos; los primeros refieren al turismo sustentable, como categoría principal; las subcategorías fueron la sustentabilidad, la conservación ambiental y las políticas públicas. Los elementos empíricos fueron la observación, entrevistas con actores clave del parque en turismo y conservación ambiental. El modelo vinculó tales subcategorías con las dimensiones estructural y posicional, que facilitaron el acercamiento con dichos actores. El análisis integral retomó los supuestos del Enfoque de Redes de Política Pública, identificando la interacción, coordinación, intercambio de información y de recursos entre los integrantes de la red formada en torno a las políticas públicas. El resultado fue un modelo que sirva como herramienta para un análisis de la realidad en dichas áreas, al visualizar los vínculos entre quienes intervienen en el turismo y la conservación ambiental. Se espera que sea referente para abordar distintas realidades en contextos diferentes, respetando y adaptándolo a sus particularidades. Se concluye, a partir del modelo, la limitante de los alcances de políticas públicas para fomentar la práctica sustentable del turismo y la conservación ambiental del parque, ante la falta de compromiso del sector público para cumplir sus responsabilidades y a los recursos limitados e intereses predominantes.
Theoretical-methodological model for the analysis of public policies that promote sustainable tourism and environmental conservation in the Valle de Bravo Water Sanctuary, Mexico
Keywords: Protected Natural Area; Public Policy Network Approach; Public Policies; Sustainability; Sustainable Tourism; Área natural protegida; Enfoque de redes de política pública; Políticas públicas; Sustentabilidad; Turismo sustentable; https://purl.org/pe-repo/ocde/ford#2.07.01